SCHOOL PRINCIPAL LEADERSHIP BASED ON PROPHETIC LEADERSHIP VALUES IN IMPROVING EDUCATOR PROFESSIONALISM - Ayu Auliyah; M. Kharis Fadillah; Ilhami Ilhami; Riyuzen Praja Tuala; Ahmad Fauzan (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
The purpose of this study is to describe the application of prophetic values in school principal leadership and examine its implications for organizational culture at SMA Negeri 2 Bandar Lampung. This study uses a qualitative approach with descriptive methods through in-depth interviews, participatory observation, and documentation studies of the principal, vice principal, administrative head, and several teachers. The results of the study show that the principal applies the value of Shiddiq through honesty and transparency, Amanah through responsibility and accountability, Fathanah through wisdom in decision making, and Tabligh through participatory communication and moral exemplary behavior. The application of these four values contributes to improving teacher professionalism, a collaborative work climate, and effective school management.